Gall-Inducing Insect Species Richness as Indicators of Forest Age and Health - Fernandes, G. Wilson; Almada, Emmanuel D; Carneiro, Marco Antonio A (Environmental entomology, 2010)
The changes in the plant community that occur during the process of succession affect the availability of resources for the community of herbivores. In this study, the richness of galling insects was evaluated in restored stands of Amazonian tropical rain forest of several ages (0–21 yr), as well as in areas of primary forest in Brazil. The richness of gallers increased with the age of the restored stands. Fifty-eight percent of the variation in the richness of galling insects was explained by forest stand age, but an increase in richness was observed at intermediate stages of succession. The greatest similarity among groups was found between the initial successional stages and intermediate ones. The results indicate a recovery of both host plants and insect community and that succession directly affects the richness and composition of these herbivores.